A new technique for trans-perirectal iodine-125 seed implantation in prostatic cancer guided by CT and 3D printed template: Two case reports - Di, Xuemin; Zhang, Hongtao; Liu, Xiaoli; Zhao, Jinxin; Gao, Zhen; Yu, Huimin; Su, Xiaohua; Liang, Yansong; Wang, Juan (Frontiers in Oncology, 2022)
Low-dose-rate prostate brachytherapy with permanent iodine-125 is an important curative treatment for low-risk prostate cancer, and it has been demonstrated that brachytherapy with permanent seeds is an effective treatment. However, differences in prostate volume, spatial location, and gland deformation between images obtained in the pre-planning phase and those obtained during the implantation procedure affect accurate delivery of the pre-planned dose. Furthermore, the complicated procedure could be a burden to elderly patients, for example, the risks associated with general anesthesia. In addition, ultrasound images are not as clear as computed tomography (CT) images with regard to identifying the location of seeds. Therefore, a new method for guidance during the procedure is urgently needed. Here, we have described a new method for precise trans-perirectal insertion of radioactive iodine-125 seeds in patients with prostate cancer under the guidance of CT and a 3D-printed template. These are some of the advantages of this technique over the standard procedure for seed implantation in the prostate: It requires only local anesthesia, the pre-planning phase can be completed before the procedure, and the operation time is considerably shorter. This report describes trans-pararectal iodine-125 seed brachytherapy for prostate cancer under local anesthesia and the guidance of a 3D printed template in two elderly patients. The dose parameters determined in the preoperative planning phase were verified postoperatively and found to be consistent. Further, the procedure was completely successfully with no major complications in both cases, and the patients’ prostate-specific antigen levels were normal at the most recent follow-up conducted 50 months after the procedure. Therefore, this technique seems promising for prostate cancer brachytherapy, and its application needs to be researched and extended further in the future.